Precisions on the ecology and chorology of Schistostega pennata (Hedw.) Webb & Mohr. in the Iberian Peninsula - Reinoso Franco, Juan; Rodríguez Oubiña, Juan; Viera Benitez, Mª del Carmen (Lazaroa, 1994)
The presence of the moss Schistostega pennata (Hedw.) Webb & Mohr. wasmentioned by different authors: Casares (1921) and Allorge (1927). Since then it has not been reported from Galicia (NW of Iberian Peninsula). The biogeographical interest of recent findings is discussed and new data is presented about the autoecology of this interesting acidofilous moss, found in very scarce quantities in the Peninsula. The main chemical characteristics of the granite excavation where this taxon usually occurs are analyzed.